2014
DOI: 10.4049/jimmunol.1303108
|View full text |Cite
|
Sign up to set email alerts
|

Polyinosinic-Polycytidylic Acid Has Therapeutic Effects against Cerebral Ischemia/Reperfusion Injury through the Downregulation of TLR4 Signaling via TLR3

Abstract: Recent reports have shown that preconditioning with the TLR3 ligand polyinosinic-polycytidylic acid (poly(I:C)) protects against cerebral ischemia/reperfusion (I/R) injury. However, it is unclear whether poly(I:C) treatment after cerebral I/R injury is also effective. We used mouse/rat middle cerebral artery occlusion and cell oxygen-glucose deprivation models to evaluate the therapeutic effects and mechanisms of poly(I:C) treatment. Poly(I:C) was i.p. injected 3 h after ischemia (treatment group). Cerebral in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 46 publications
5
76
1
Order By: Relevance
“…21,32 After the blood vessels and meninges removed, the cortices of postnatal day 1 mice were digested using 0.25% trypsin-EDTA (Life Technologies, Birmingham, MI) for 5 min and stopped by heat-inactivated FBS. After triturated using a P-1000 plastic tip, the cells suspension was cultured in DMEM containing 10% heatinactivated FBS (Gibco, Life Technologies Corporation), 50 U/ml penicillin and 50 mg/ml streptomycin.…”
Section: Cell Sorting and In Vitro Cell Culturementioning
confidence: 99%
“…21,32 After the blood vessels and meninges removed, the cortices of postnatal day 1 mice were digested using 0.25% trypsin-EDTA (Life Technologies, Birmingham, MI) for 5 min and stopped by heat-inactivated FBS. After triturated using a P-1000 plastic tip, the cells suspension was cultured in DMEM containing 10% heatinactivated FBS (Gibco, Life Technologies Corporation), 50 U/ml penicillin and 50 mg/ml streptomycin.…”
Section: Cell Sorting and In Vitro Cell Culturementioning
confidence: 99%
“…On the other hand, Bax is a proapoptotic protein which can trigger cell death by transferring to the mitochondrial membrane and inducing cytochrome c release [85] . The Bcl2 family maintains a stabilization of the balance between Bcl-2 and Bax [86][87][88][89] . Therefore, the effects of both melatonin and resveratrol have been examined on the level of Bcl-2 and Bax in the hippocampal CA1 region.…”
Section: Discussionmentioning
confidence: 99%
“…As indicated earlier (see Section 2.3), TLR3 has previously been implicated in mediating loss of BBB integrity and contributing to neuropathology in a mouse model of WNV infection [30]. Nonetheless, recent studies have reported protective effects of poly(IC) treatment in brain I/R injury models [87][88][89]. This was linked to the capacity of TLR3 signalling in human astrocytes to drive expression of anti-inflammatory cytokines, such as Ifn-, which act as neuroprotective factors [87,88].…”
Section: I/r Injury In the Brainmentioning
confidence: 99%
“…For example, in a mouse model, poly(IC) treatment following I/R injury improved recovery of brain function, as assessed by neurological behaviour [89].…”
Section: Therapeutic Implicationsmentioning
confidence: 99%